Zileuton use and phenotypic features in asthma. (February 2020) - Thalanayar Muthukrishnan, P.; Nouraie, M.; Parikh, A.; Holguin, F.
Abstract: Zileuton, a 5-lipoxygenase (5LPO) inhibitor exerts a broad influence in the arachidonic acid (AA) pathway by blocking upstream molecules that otherwise would lead to production of an array of inflammatory leukotrienes (LT) A4-E4. Hence, it has the potential to be a drug suitable to treat complicated asthmatics. Studies have shown modest response rates for zileuton in asthmatics. Objective: We sought to study our hypothesis that response to zileuton varies across specific asthmatic phenotypes. Methods: We retrospectively analyzed data from 129 patients with asthma that were prescribed zileuton at the University of Pittsburgh's Comprehensive Lung Clinic. A total of 75 patients from the above population had requisite lung function data and zileuton usage that would help assess a drug response effect. A zileuton responder was defined as having at least or greater than 5% annualized increase in post-bronchodilator FEV1% from baseline. Using a multivariate logistic regression analysis, we determined the association between responder status and the underlying phenotypic characteristics. Results: Using generalized estimating equations (GEE) analysis of 331 individual lung function test data-points as well as logistic regression analysis for predictors of 5% or more annualized increase in FEV1%, 21 of 75 patients (28%) met criteria for having a differential response to zileuton. Severe asthma was associated less often with responder status (OR 0.12; p 0.004). Obesity was less often associated with responder status, however did not reach significance (OR 0.46; p 0.15). Conclusion: In this retrospective study, zileuton response varies across asthmatics, with poorer response rates being associated with those with severe asthma and possibly obesity. Although prescription trends for zileuton may predominate amongst severe asthmatics, this tendency does not seem to mirror the actual likelihood to respond. As against the trivial role for zileuton per current GINA algorithms, our study brings forward a notion that zileuton may well be considered along with LTRAs (like montelukast) for non-severe asthma.